A cyclic octithiophene containing β, β′-linkages. Issue 28 (6th March 2015) - Asai, Kengo; Fukazawa, Aiko; Yamaguchi, Shigehiro
Abstract : A cyclic octithiophene containing β, β′-linkages showed red-shifted fluorescence compared to α-quaterthiophene and a spin delocalization in the radical cation state. Abstract : A cyclic octithiophene containing two β, β′-linkages was synthesized. Due to the large structural change in the excited state, this compound exhibited bathochromically shifted fluorescence. It also showed a small difference between the first and second oxidation potentials, indicative of spin delocalization through the β, β′-linkage in the one electron-oxidized state.